Pourquoi mobiliser l’historicité en didactique des langues et des cultures ? - Alice Burrows (Recherches en didactique des langues et des cultures)
Historicity is a concept that is not often referred to in French Applied Linguistics (FAL). Defined in this article as the socialized experience of time, historicity is used to account for the practices of transmitting a shared history within a community. However, FAL maintains a complex relationship with its history and modes of transmission, particularly in the initial training of teachers of French as a foreign language. This article seeks to identify the characteristics of the production of this history, as well as the challenges of its dissemination within the discipline. To do so, the current state of research in the history of FAL helps to outline the definitions proposed by Alexandre Escudier’s article to understand the contributions of analyses based on the concept of historicity.